Corybas geminigibbus, a new addition to the orchid flora of Sumatra - Mustaqim, Wendy A. (2024)
Corybas is an orchid genus of 154 species distributed from India to South China, the Western Pacific, and New Zealand. Sumatra is home to eight species, five of which are endemic. However, the true diversity is likely underestimated due to limited exploration in some parts of the island. During a recent exploration in the northern Gayo Plateau near the northern tip of the island, a Corybas species was discovered that did not match any previously known species. Further identification through specimen comparison and literature review confirmed that the species is Corybas geminigibbus. It was found growing in montane bogs. This discovery marks the second bioregion in Indonesia where this species has been recorded and the ninth Corybas species on the island. The finding also provides additional evidence of floristic similarities, suggesting past geological connections between northern Sumatra and mainland Asia. A detailed description, discussion, and photographs are provided.